Effects of Strigolactone on Torreya grandis Gene Expression and Soil Microbial Community Structure Under Simulated Nitrogen Deposition - Yu, Chenliang; Wang, Qi; Zhang, Shouke; Zeng, Hao; Chen, Weijie; Chen, Wenchao; Lou, Heqiang; Yu, Weiwu; Wu, Jiasheng (Frontiers in Plant Science, 2022)
Nitrogen enters the terrestrial ecosystem through deposition. High nitrogen levels can affect physical and chemical properties of soil and inhibit normal growth and reproduction of forest plants. Nitrogen modulates the composition of soil microorganisms. Strigolactones inhibits plant branching, promotes root growth, nutrient absorption and promotes arbuscular fungal mycelia branching. Plants are subjected to increasing atmospheric nitrogen deposition. Therefore, it is imperative to explore the relationship between strigolactone and nitrogen deposition of plants and abundance of soil microorganisms. In the present study, the effects of strigolactone on genetic responses and soil microorganisms of Torreya grandis, under simulated nitrogen deposition were explored using high-throughput sequencing techniques. T. grandis is a subtropical economic tree species in China. A total of 4,008 differentially expressed genes were identified in additional N deposition and GR24 treatment. These genes were associated with enrichment of multiple GO terms and metabolic pathways. Both additional nitrogen deposition and GR24 treatment modulated the content of nutrient elements. A total of 1,402,819 clean reads and 1,778 amplicon sequence variants (ASVs) were generated through Bacterial 16S rRNA sequencing. Random-forest classification revealed that Legionella, Lacunisphaera, Klebsiella, Bryobacter and Janthinobacterium were significantly enriched in the soil in the additional N deposition group and the GR24 treatment group. Co-occurrence network analysis showed significant differences in composition of soil microbial community under different treatments. These results indicate a relationship between N deposition and strigolactone effect. The results provide new insights on the role of strigolactone in plants and composition of soil microorganisms under nitrogen deposition.